TiO2 Nanoparticles Prepared by MOCVD: Effect of Temperature, Flowrate, and Precursor. - Othman, Siti Hajar; Abdul Rashid, Suraya; Abdullah, Norhafizah; Mohd Ghazi, Tinia Idaty (2013)
Titanium dioxide nanoparticles were produced by metal organic chemical vapour deposition method. The effect of deposition temperatures (400–900 °C), flowrates of the carrier gas (200–600 mL/min), and the precursors [titanium (IV) butoxide (TBOT) and titanium tetraisopropoxide (TTIP)] on the particle size, surface area, crystallinity, and photocatalytic activity of the samples were investigated. The results showed that the particle size decreased and the surface area increased with increasing deposition temperature from 400 to 700 °C. However, particle size increased and surface area decreased with increasing temperature from 700 to 900 °C because of sintering effects. The phase transition from anatase to rutile occurred at temperatures above 700 °C. Increasing flowrate of carrier gas reduced particle size, increased surface area, and enhanced crystallinity of the titanium dioxide nanoparticles. Sample produced at 900 °C has the best photocatalytic activity compared with other samples including the commercial Degussa P25. Crystallinity was found to have a more significant role on photocatalytic activity in contrast to particle size. It is noteworthy that for samples deposited at 700 °C, the TBOT precursor was found to produce smaller and more uniform particle size compared with the TTIP precursor. However, it is easier to form crystalline phase using TTIP than TBOT.